Faculty of Computer Science and Information Technology ICT Strategic Plan - Mohd. Noor, Zaimah (2004)
Organisations today are challenged to compete on a global level to achieve more by using fewer resources. With the advancement in technology, organisations have strived to find ways to leverage on technology to achieve excellence. Clear examples are how organisations use technology in procurement, human resource management and communication among others. However, research has found that most organisations only obtained 20%-30% of the potential benefits from the investment in technology. This gap between the investment and the benefits needs to be addressed by integrating all business components to form a practical strategic IT plan. The Faculty of Computer Science and lnformation Technology and its departments are embarking on the development of a strategic plan on how best to leverage on technology. Undoubtedly, there are numerous areas where technology can assist such as Operations Management, lnformation Gathering and Sharing amongst others. This is the proposing to develop the ICT Strategic Plan for FSKTM. The approach to lnformation Technology Strategic Planning will strongly complement FSKTM's ICT environment. The approach combines the best methods to develop an appropriate FSKTM's ICT Strategic Plan, through the experiences in ISP development for other Government departments in Malaysia.